English language vocabulary learning strategies employed by young ESL learners / Harpreet Kaur - Harpreet , Kaur (2019)
This study investigates the effectiveness of vocabulary learning strategies employed by Year Two students learning English in an international school in the city of Shah Alam. The study employed a mixed methods design in two phases: an experiment to compare the vocabulary learning strategies used by participants and data collection via questionnaire and interview. The participants were 40 mixed-nationality students from higher-income families, comprising twenty students each from two Year Two classes. In the experiment phase, one class was categorised as the treatment group whereas the other class was the control group. Both groups were given a pre-test to identify the level of their vocabulary knowledge. The participants from the treatment group then received an intervention. However, the participants from the control group did not receive any treatment and their lessons were conducted as usual. After the treatment group received the intervention, both groups were required to answer the post-test questions. The theoretical framework applied in this research was Schmitt’s (1997) classification of vocabulary learning strategies. In the second phase, the researcher utilised a pictorial representation questionnaire and an interview to obtain the findings for this research. A key finding is that although the participants were young, they displayed an indirect approach to learning as they employed all the other strategies which were taught to them after the intervention. Nevertheless, this research also indicates that young learners can be taught strategies which are appropriate for their age and needs. Results of this study also indicate that the choice of vocabulary strategies differs based on the participants’ proficiency level. Most participants from the highest proficiency group preferred cognitive strategies over memory strategies while the participants from the low proficiency group tended to prefer the method of segmenting words and social strategies. Lastly, the findings suggest that vocabulary learning strategies help to aid learners’ vocabulary learning. The researcher hopes that this research will bring about a better understanding of vocabulary learning strategies, and that those who are involved in educating students, whether at international or national schools, will recognise that there is much to be gained from the employment of these strategies.